TRANSPORT OF PINATUBO AEROSOLS TO THE ARCTIC REGION : LIDAR MEASUREMENTS IN ALASKA, WINTER 1991/1992 - イワサカ, ヤスノブ; ハヤシ, マサヒコ; シバタ, タカシ; マツナガ, カツジ; ナガタニ, マサヒロ; ナカダ, ヒロシ; モリ, イクコ; オジオ, テツロウ; フジワラ, モトオ; アキヨシ, エイジ; ヤスマツ, サトシ; ヤマザキ, コウジ; et al. (National Institute of Polar Research, 1994)
P(論文) The concentration of stratospheric aerosols observed with a lidar in Alaska increased from December 1991 to March 1992. The measurements suggested that particulate matter injected into the stratosphere through the eruption of Pinatubo (Philippines, June 1991) was transported to high latitudes and descended there. The speed of descending motion of the aerosol layer in Alaska was about 50 m/day, larger than the value in mid-latitudes. departmental bulletin paper